Pengaruh Model Project Based Learning Terhadap Ecoliteracy Peserta Didik Dalam Pembelajaran IPS - Evi Luthvia Sholihat (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2023)
Garbage pollution is a crucial environmental issue that has garnered significant attention from the global community. One of the methods employed to combat this issue is to promote environmental awareness through eco-literacy activities in schools. This research explores the connection between using project-based learning models and eco-literacy among students in social studies classes. A quantitative method was used in this study, employing a quasi-experimental design with a non-equivalent control group design. The research was conducted at SMPIT Imam Bukhari, with the experimental class being VIII-D and the control class being VIII-C. The practical course utilised a project-based learning model, while the control class used a problem-based learning model. Based on the data processing and analysis, it was observed that there was an increase in the eco-literacy of students in the experimental class, as evidenced by the Sig. (2-tailed) value of 0.000 <0.05 and the average pretest and posttest scores of 67.07 and 83.13, respectively. Similarly, the control class using the problem-based learning model also experienced a significant increase in eco-literacy, with a Significant (2-tailed) value of 0.000<0.05 and average pretest and posttest scores of 66.77 and 70.23, respectively. However, a substantial difference was observed in the eco-literacy of students between the experimental and control classes after the treatment (post-test), as seen from the Sig. (2-tailed) value of 0.000 <0.05. The average post-test score for the experimental class was 83.13, while the control class recorded an average post-test score of 70.23.Keywords: Eco-literacy, project-based learning model, social studies learning.